2023
DOI: 10.1159/000531207
|View full text |Cite
|
Sign up to set email alerts
|

Auditory and Vestibular Findings in Brazilian Adults Affected by COVID-19: An Exploratory Study

Patrícia Arruda de Souza Alcarás,
Maria Cristina Alves Corazza,
Larissa Vianna
et al.

Abstract: <b><i>Introduction:</i></b> The aim of the study was to describe auditory and vestibular findings in Brazilian adults after COVID-19 in a municipality from the outskirts of the São Paulo state. <b><i>Methods:</i></b> This was a transversal and exploratory study comprising sixteen participants infected by the SARS-CoV-2 virus, confirmed through RT-PCR detection, aged 20 to 55 years. Subjects underwent anamnesis, vestibular and auditory testing. Fisher’s exact test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
1
1
Order By: Relevance
“…The data we present demonstrate that individuals testing positive for COVID-19 are over twice as likely to develop vestibular symptoms compared to the general population. Although our data estimates the overall prevalence of vestibular disorder amongst these patients at between 1% and 3%, other studies have estimated the self-reported numbers to reach as high as over 40% ( 7 , 14 , 15 ). One must also consider individuals whose vestibular symptoms remain undiagnosed, those who did not seek medical attention for their vestibular symptoms during our observation window, and those who were never tested and diagnosed with COVID-19.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The data we present demonstrate that individuals testing positive for COVID-19 are over twice as likely to develop vestibular symptoms compared to the general population. Although our data estimates the overall prevalence of vestibular disorder amongst these patients at between 1% and 3%, other studies have estimated the self-reported numbers to reach as high as over 40% ( 7 , 14 , 15 ). One must also consider individuals whose vestibular symptoms remain undiagnosed, those who did not seek medical attention for their vestibular symptoms during our observation window, and those who were never tested and diagnosed with COVID-19.…”
Section: Discussioncontrasting
confidence: 77%
“…However, other head and neck symptoms related to COVID-19, particularly of the cochleovestibular system, also necessitate our attention, as up to 58% of patients affected by COVID-19 reported vestibular symptoms and 9% reported auditory symptoms upon initial diagnosis ( 6 ). These symptoms have also been found to affect women disproportionately ( 7 ). Jeong et al have demonstrated a mechanism of viral entry into the cells of the cochleovestibular end organs via the angiotensin-converting enzyme 2 receptor pathway, providing further insight into the impact it has on hearing loss, tinnitus, and vertigo ( 8 10 ).…”
mentioning
confidence: 99%